2013
DOI: 10.1519/jsc.0b013e3182a95343
|View full text |Cite
|
Sign up to set email alerts
|

FMS™ scores change with performers’ knowledge of the grading criteria – Are general whole-body movement screens capturing “dysfunction”?

Abstract: Frost, DM, Beach, TAC, Callaghan, JP, and McGill, SM. FMS scores change with performers' knowledge of the grading criteria-Are general whole-body movement screens capturing "dysfunction"? J Strength Cond Res 29(11): 3037-3044, 2015-Deficits in joint mobility and stability could certainly impact individuals' Functional Movement Screen (FMS) scores; however, it is also plausible that the movement patterns observed are influenced by the performers' knowledge of the grading criteria. Twenty-one firefighters volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 27 publications
1
45
0
1
Order By: Relevance
“…The participants were video-recorded from the frontal and sagittal planes and the trials were graded at a later time. This is a commonly used [6,[19][20][21][22][23][24], reliable [25] method for scoring the FMS. Participants were not familiarized with the FMS prior to testing as knowledge of the FMS scoring scheme affects performance [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were video-recorded from the frontal and sagittal planes and the trials were graded at a later time. This is a commonly used [6,[19][20][21][22][23][24], reliable [25] method for scoring the FMS. Participants were not familiarized with the FMS prior to testing as knowledge of the FMS scoring scheme affects performance [6].…”
Section: Methodsmentioning
confidence: 99%
“…Each of the tasks may be attempted three times. Coaching cues and/or corrections are not provided, nor are the specific grading criteria made known to those being assessed [6]. The clearing tests are each associated with a functional test: Shoulder Impingement with SM; Spinal Extension with TSPU; and Spinal Flexion with RS.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also highlighted the difference between years of experience and the number of tests a rater has administered, stating that the latter is likely of greater relevance to improving reliability. Five studies [11,18,20,21,29] included information as to the raters' experience (years of clinical practice, number of FMS tests performed, or level of certification), which allowed comparison of test reliability based on these variables. Four studies [11,18,20,29] suggested the experience of the rater did not influence the inter-rater reliability.…”
Section: Functional Movement Screenmentioning
confidence: 99%
“…Five studies [11,18,20,21,29] included information as to the raters' experience (years of clinical practice, number of FMS tests performed, or level of certification), which allowed comparison of test reliability based on these variables. Four studies [11,18,20,29] suggested the experience of the rater did not influence the inter-rater reliability. Additionally, Smith et al [11] observed good intra-rater reliability (ICCs [0.80) for all raters, regardless of experience.…”
Section: Functional Movement Screenmentioning
confidence: 99%
See 1 more Smart Citation